2016
DOI: 10.1007/5584_2016_220
|View full text |Cite
|
Sign up to set email alerts
|

Associations of CYP1A2 Polymorphisms with the Risk Haplotypes in Lung Cancer in the Slovak Population

Abstract: Phase I enzymes, including cytochrome P450, family 1, subfamily A, and polypeptide 2 (CYP1A2), are involved in the activation of carcinogens to reactive intermediates that are capable of binding covalently to DNA to form DNA adducts, potentially initiating the carcinogenic process. The aim of present study was to investigate the association of CYP1A2 gene polymorphisms and haplotypes with lung cancer risk. A case-control study was carried out on 105 lung cancer patients and 189 controls. To investigate three C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Only one study has investigated the association of these three CYP1A2 polymorphisms and haplotypes with cancer risk. Matakova et al ( 31 ) studied the risk of lung cancer in a case-control study of 105 patients with lung cancer and 189 controls. The study reported a significant association of the CYP1A2 rs2470890 and rs2422299 polymorphisms with lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study has investigated the association of these three CYP1A2 polymorphisms and haplotypes with cancer risk. Matakova et al ( 31 ) studied the risk of lung cancer in a case-control study of 105 patients with lung cancer and 189 controls. The study reported a significant association of the CYP1A2 rs2470890 and rs2422299 polymorphisms with lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Three tagged SNPs, capturing common variability of the CYP1A2 gene, were adopted according to the approach described by Matakova et al ( 31 ). The common variability given by the presence of polymorphic sites with minor allele frequency >10% was studied.…”
Section: Methodsmentioning
confidence: 99%